Perubahan Kebudayaan Masyarakat Petani-Nelayan Pasca Pembangunan Pelabuhan Perikanan Pantai di Sadeng, Yogyakarta - Rahayuwati Rahayuwati; Mudjahirin Thohir; Af'idatul Lathifah (Endogami: Jurnal Ilmiah Kajian Antropologi, 2020)
Sedekah laut ritual (sea thanksgiving) is an annual tradition which is held in the Islamic month of Suro by fishing communities in Indonesia, including the fishing community in Sadeng, Gunungkidul, DIY. This ritual functions as a means for the fishermen to ask for safety and sustenance to The Almighty God and to communicate symbolically with Nyi Roro Kidul who is the ruler of the south coast. Therefore, this ritual becomes a moral obligation for the fishing community. There is an interesting fact which can be uncovered regarding how this ritual became a tradition in the first place. Once an agrarian society, the people in Sadeng switched job into becoming fishermen after the establishment of Sadeng Fisheries Port (PPP) in 1992. This establishment brought huge impacts on the lives of the local people, including the emergence of sedekah laut, which is a common tradition for a fishing community. In this ethnographic study, the writer wants to examine what this sedekah laut is all about as well as to identify its meaning and function for Sadeng community. It can be drawn from the results of this study that the meaning of this ritual is communicating with Nyi Roro Kidul in order to ask for safety and to get plenty of earnings from fishing. Sedekah laut also functions as a means to fix social fragmentation, to redefine values, as well as to restore balance and solidarity between groups within the community. That way, Sadeng people can live a peaceful and content life.